Reframing Roman Liturgy A Critical Edition of Onofrio Panvinio's Vetusti aliquot rituales libri - Malesevic, Filip (Peter Lang International Academic Publishing Group, 2022)
This book presents a critical edition of a collection of liturgical manuscripts that the Augustinian friar Onofrio Panvinio (1530-1568) assembled in the 1560s for the Cardinal Alessandro Farnese as well as for Hans Jakob Fugger in Augsburg. Onofrio Panvinio is primarily known for his antiquarian studies about ancient Rome and for his edition of Bartolomeo Platina's Lives of the Popes. His preoccupation with the Roman rite, however, remains until today largely unnoticed by modern scholarship. This edition of Panvinio's Vetusti aliquot rituales libri highlights his interests in the development of Roman liturgy during the last sessions of the Council of Trent (1545-1563) by presenting the various documentary as well as cultural layers of Panvinio's collection of Roman ritual manuscripts.